Recent Progress in Daytime Radiative Cooling: Advanced Material Designs and Applications. Issue 4 (25th February 2022) - Zhang, Qian; Wang, Shuaihao; Wang, Xueyang; Jiang, Yi; Li, Jinlei; Xu, Weilin; Zhu, Bin; Zhu, Jia
Abstract: Passive daytime radiative cooling (PDRC) is emerging as a promising cooling technology. Owing to the high, broadband solar reflectivity and high mid‐infrared emissivity, daytime radiative cooling materials can achieve passive net cooling power under direct sunlight. The zero‐energy‐consumption characteristic enables PDRC to reduce negative environmental issues compared with conventional cooling systems. In this review, the development of advanced daytime radiative cooling designs is summarized, recent progress is highlighted, and potential correlated applications, such as building cooling, photovoltaic cooling, and electricity generation, are introduced. The remaining challenges and opportunities of PDRCs are also indicated. It is expected that this review provides an overall picture of recent PDRC progress and inspires future research regarding the fundamental understanding and practical applications of PDRC. Abstract : Passive daytime radiative cooling (PDRC), as an emerging cooling technology, has excellent potential to mitigate global warming. The development of advanced PDRC designs and potential correlated applications are summarized in this review. This review further discusses the challenges and opportunities and puts forward some personal perspectives on the design of passive daytime radiative coolers.